1969
DOI: 10.2136/sssaj1969.03615995003300050010x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drying on Soil Strength Parameters

Abstract: The influence of drying on the magnitudes of soil strength parameters C and ϕ was determined for three cohesive soils. Shear strength measurements were made using a modified laboratory triaxial apparatus for three different soil types on samples prepared in the laboratory. All samples of a given soil type were molded at the same soil water content and to the same bulk density. Samples were dried slowly to soil water contents between the 1/3‐bar soil water suction level and air dryness.The criterion used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

1972
1972
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…O comportamento hídrico da toposseqüência sugere menores restrições físicas para o crescimento e desenvolvimento das raízes com o aumento dos teores de argila, o que é confirmado pela presença de valores de densidade abaixo do valor crítico (Figura 3 e Quadro 1). Com a maior drenagem nos solos com menor teor de argila, o incremento em resistência do solo à penetração ocorre provavelmente associado à maior coesão e ângulo de fricção interna (Camp & Gill, 1969) e à maior fricção interpartículas devido ao aumento de densidade do solo (Vepraskas, 1984). Ao atingir o ponto de murcha permanente (potencial da água no solo de -15.000 c.c.a.…”
Section: Resultsunclassified
“…O comportamento hídrico da toposseqüência sugere menores restrições físicas para o crescimento e desenvolvimento das raízes com o aumento dos teores de argila, o que é confirmado pela presença de valores de densidade abaixo do valor crítico (Figura 3 e Quadro 1). Com a maior drenagem nos solos com menor teor de argila, o incremento em resistência do solo à penetração ocorre provavelmente associado à maior coesão e ângulo de fricção interna (Camp & Gill, 1969) e à maior fricção interpartículas devido ao aumento de densidade do solo (Vepraskas, 1984). Ao atingir o ponto de murcha permanente (potencial da água no solo de -15.000 c.c.a.…”
Section: Resultsunclassified
“…However, as one might observe in surface plots of SR as a function of both bulk density and water content (Imhoff et al, 2000;Sojka et al, 2001) the influence of bulk density over SR characteristics increases as the soil water content decreases. The decrease in SR with the increase in θv is due to the reduction in cohesion and in the angle of internal friction as soil water content increases (Camp & Gill, 1969). The increase in SR with Db is attributed to the effect of compaction over soil matrix, and the increase in interparticle friction as soil particles become closer with soil compaction (Vepraskas, 1984;Sojka et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…same mechanical and environmental conditions but different texture behave differently. Camp and Gill [2] and Smith [3] reported that shear strength parameters of fine grained soils decreased with increasing moisture content. However, the soil density was concurrently decreasing as the moisture content was increased.…”
Section: Effect Of Soil Physical Propertiesmentioning
confidence: 99%